Are Prophylactic Antibiotics Necessary in Primarily Closed Lacerated Wounds? (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: wound infection; antibiotic prophylaxis; lacerated wounds; contaminated wounds; wound length; wound debridement; copious irrigation